The effectiveness evaluation of job-shop scheduling based on Theory of Constraints (TOC) under demand variation - Kasemset,C. (2015)
© 2013 IEEE. This study aims to present the effectiveness evaluation of job-shop scheduling based on TOC concept under demand variation using simulation technique. Two schedule performance measurements under uncertainty, schedule robustness and performance, are used in comparing the performance of schedule based on TOC and traditional method (minimizing Cmax). Simulation test scenarios are carried out by applying different distribution of demand as Poisson and uniform distributions with two case problems as single and double bottlenecks cases. The results show that the schedule based on TOC concept is superior to the schedule from traditional method when demand variation is increased and the production system is more complicated as can be observed from the results of double bottlenecks case.